Bernard-Soulier Syndrome with Severe Bleeding: Absent Platelet Glycoprotein lb alpha Due to a Homozygous One-base Deletion - Li, Chaoyang; Pasquale, Dominick N; Roth, Gerald J (Thrombosis and Haemostasis, 1996)
Bernard-Soulier syndrome is a rare congenital platelet disorder that affects a surface membrane adhesion receptor, glycoprotein (GP) Ib-V-IX. Both the genetic defects and the bleeding diatheses associated with the syndrome are heterogeneous due, in part, to the complexity of the involved receptor which consists of four different members, GPs: Ibα-Mr 143 K (contains the von Willebrand factor-binding site), Ibβ-Mr 22 K, V-Mr 83 K and IX-Mr 20 K. We studied a kindred that includes a 40 year-old man with severe Bernard-Soulier syndrome: life-threatening gastrointestinal bleeding, thrombocytopenia, giant platelets and absent ristocetin-dependent platelet aggregation. By Southern blotting, PCR amplification/sequencing, hetero-duplex analysis, and allele-specific oligonucleotide hybridization, the Ib-V-IX genes were analyzed, and the molecular genetic defect was defined as a one-base deletion in the GPIbα gene, involving an adenine of codon 19. The mutation, K19R, homozygous in the propositus and heterozygous in the available unaffected relatives, leads to a frame shift in codons 19-21 and a premature stop codon after codon 21. No functional GPIbα can be produced from the mutant allele, implying that the platelets of the affected patient lack all GPIbα. Within the spectrum of Bernard-Soulier syndrome, this patient’s disorder exemplifies a severe or “classic” extreme; an “experiment of Nature” that illustrates the effect of a complete deficiency of the ligand-binding chain (GPIbα) of the GPIb-V-IX receptor.